DISCRIMINATIVE MODELS OF THE POSSIBILITY OF VARIOUS FORMS OF URTICARIA OCCURRENCE AND CHARACTERISTICS OF THE COURSE IN UKRAINIAN MEN DEPENDING ON THE CHARACTERISTICS OF THE STRUCTURE AND BODY SIZE - Aladwan, A.M.A.; Skoruk, R.V.; Kyrychenko, I.M.; Dmytrenko, S.V.; Smolko, D.G. (World of Medicine and Biology, 2023)
In Ukrainian men, on the basis of the characteristics of body structure and size, reliable discriminative models were built, which allow with a high probability to classify the subjects as “typical” for practically healthy or urticaria patients (correspondingly, the correctness of 83.6 % of cases, Wilks’ Lambda statistic=0.113). Taking into account the structure and body size indices among men with urticaria, a reliable interpretation of the obtained classification indices is possible only between acute and chronic forms of the disease (correspondingly, the correctness of 60.0 % of cases, Wilks’ Lambda statistic=0.620).